Effect of Antibiotic Exposure on Upper Respiratory Tract Bacterial Flora - Korkmaz, Hakan; Çetinkol, Yeliz; Korkmaz, Mukadder; Çalgın, Mustafa Kerem; Kaşko Arıcı, Yeliz (Medical science monitor, 2022)
BACKGROUND The human microbiota modulates the immune system and forms the surface flora. Antibiotic administration causes dysbiosis in the intestinal flora. It is not clear if antibiotic administration in the community effects the upper airway flora in the mid-term or long-term. This study aims to define long-term influence of antibiotics on upper airway flora. MATERIAL AND METHODS In this prospective study, aerobic microbiological analysis of nasal and nasopharyngeal surfaces was performed. Antibiotic administration history of the last 6 months was retrieved using the social insurance database. Culture results of antibiotic-treated and antibiotic-naïve subjects were compared by Pearson's chi-square test or Fisher's exact test. RESULTS A total of 210 subjects were included in the study. Normal flora were documented in 86 nasal swabs and 99 nasopharyngeal swabs. Most of the remaining cases demonstrated gram-positive bacterial overgrowth. There were 113 subjects who did not receive any antibiotic, and 93% of the remaining 97 patients received broad-spectrum antibiotics. Statistical analysis showed that nasal and nasopharyngeal flora did not change upon antibiotic administration, but antibiotic administration during the last month caused increased methicillin resistance development of coagulase-negative Staphylococcus and Staphylococcus aureus microorganisms. CONCLUSIONS Antibiotic exposure did not lead to perturbations in general composition of upper airway flora within 6 months, although the incidence of methicillin resistance in coagulase-positive and -negative Staphylococci demonstrated significant increases when patients received antibiotic during the last month. This should be considered in case of broad-spectrum antibiotic administration, since methicillin resistance increases the morbidity and mortality of nosocomial Staphylococcus infections.